EFFECT OF NITROGEN LEVELS AND SPACING ON YIELD ATTRIBUTES, YIELD AND QUALITY PARAMETERS OF BABY CORN (ZEA MAYS) - GOSAVI, S.P.; BHAGAT, S.B. (Annals of Agricultural Research, 2014)
A experiment was conducted during rabi season during 2005-06 on lateritic soil, at Agronomy Farm, College of Agriculture, Dapoli, to study the effect of nitrogen levels (0,50,100,150 and 200 kg ha and spacing (60x20cm, 45x20cm and 30x20cm) on the performance of yield attributes,yield and quality parameter of baby corn study revealed that spacing 60 x 20 cm was pat par with 45 x 20 cm recorded significantly higher values of yield attributing characters over the spacing of 30 x 20 cm. The spacing of 45 x 20 cm recorded significantly higher baby corn yield with and without husk than the remaining spacing’s. The length of baby corn cob, number of cobs per plant and baby corn (cob) weight withouthusk increased significantly with the increase in nitrogen levels up to 150 kg/ha. Application of 200kg N/ha recorded significantly higher baby corn yield with husk, green fodder yield and total biomass production (q/ha) than rest of the nitrogen levels. The wider spacing of 60 x 20 cm recorded significantly higher protein and sugar content than the narrower spacing. Application of 200 kg N/ ha recorded significantly higher protein %, in baby corn than rest of the nitrogen levels. The further application of 150 kg/ha and 200 kg/ha nitrogen were at par and recorded significantly higher sugar content than the remaining nitrogen levels viz. 100 k/ha, 50 k/ha and control.